The threefold logic of advanced architecture : conformative, distributive and expansive protocols for an informational practice: 1990-2020 - Gausa, Manuel; Vivaldi, Jordi (2021)
"This book argues that during the last 30 years, Advanced Architecture has consolidated an interactive and informational logic that differs from that of Modernity and Postmodernity. This logic is threefold; it is modulated through three coexisting protocols -modes of action- whose peaks of intensity occur in three different decades: Conformative Protocols (1990-2000), Distributive Protocols (2000-2010) and Expansive Protocols (2010-2020)"--